2021
DOI: 10.3390/nu13041320
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast: A Crucial Meal for Adolescents’ Cognitive Performance According to Their Nutritional Status. The Cogni-Action Project

Abstract: This study aimed to determine whether pupils who have breakfast just before a cognitive demand, do not regularly skip breakfast, and consume a high-quality breakfast present higher cognitive performance than those who do not; furthermore, to establish differences according to their nutritional status. In this study, 1181 Chilean adolescents aged 10–14 years participated. A global cognitive score was computed through eight tasks, and the body mass index z-score (BMIz) was calculated using a growth reference for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 69 publications
3
14
0
2
Order By: Relevance
“…Despite the documented benefits of breakfast consumption, skipping breakfast was found to be more common and the percentage of participants skipping regular breakfast was 76⋅9 %. It has also been reported in various other studies that the frequency of skipping breakfast is higher in girls ( 74 , 75 ) , and breakfast skippers tend to consume more fast food, leading to increased weight gain from adolescence to adulthood. These unhealthy dietary habits are also seen in various other such studies done in the past ( 76 – 78 ) .…”
Section: Discussionsupporting
confidence: 58%
“…Despite the documented benefits of breakfast consumption, skipping breakfast was found to be more common and the percentage of participants skipping regular breakfast was 76⋅9 %. It has also been reported in various other studies that the frequency of skipping breakfast is higher in girls ( 74 , 75 ) , and breakfast skippers tend to consume more fast food, leading to increased weight gain from adolescence to adulthood. These unhealthy dietary habits are also seen in various other such studies done in the past ( 76 – 78 ) .…”
Section: Discussionsupporting
confidence: 58%
“…Likewise, another investigation conducted among European adolescents reported that higher diet quality scores were linked with attention capacity, and the authors also indicated that dietary patterns were a better determinant of executive function than the analysis of single nutrients [47]. Furthermore, Peña et al conducted a cross-sectional project with Chilean schoolchildren and reported that students with healthy food habits (i.e., who have a breakfast of high quality) presented better cognitive performance compared with students who did not [21]. Moreover, the findings of another study indicated that poorer food choices were related with reduced performance in verbal and cognitive ability [48].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that dietary habits during childhood are related to learning processes [15] and cognition in schoolchildren [20]. A recent study reported that schoolchildren with better food habits had better cognitive performance [21]. Recently, it was shown that good food habits were positively associated with academic performance [22].…”
Section: Introductionmentioning
confidence: 91%
“…Breakfast may improve neuronal activity (31) and cognitive control (e.g., working memory and attentional capacities) (32), which in turn can influence school 35) demonstrated that breakfast consumption had a positive influence on students' cognitive functions and school performance. Furthermore, Peña-Jorquera et al (36) indicated that adolescents who eat breakfast before cognitively demanding activities and who regularly include a high-quality breakfast have higher cognitive performance than their counterparts who do not. A possible reason for these findings could lie in the association between skipping breakfast and an increased likelihood of depression, anxiety, psychological distress, and stress in adolescence (37), which can negatively affect school performance.…”
Section: Breakfast Consumption and High Perceived School Performancementioning
confidence: 99%